Protein purification and cDNA cloning of suGF1 : a sea urchin nuclear DNA-binding factor - Scherer, Sonja Daniela (Department of Molecular and Cell Biology, 2016)
The upstream regulatory regions of numerous genes contain contiguous deoxyguanosine residues (G·C-rich sequences) which have been implicated in the regulation of gene expression, since they may involve alterations in their DNA structure, the binding of G-string factors and in some cases even the displacement of a nucleosome positioned over this area. A poly( dG).poly( de)-binding protein (suGF1) has previously been identified and purified on a small scale from embryonic nuclear extracts of the sea urchin Parechinus angulosus (1, 2). suGF1 binds in vitro to the H1-H4 intergenic region of the early histone gene battery, and the recognition site contains 11 contiguous Gs which are incorporated into a positioned nucleosome core in vitro. suGFI may be a member of a family of Gstring factors which could be involved in the developmental regulation of unrelated genes in various organisms. Prior to the commencement of this project no protein or DNA sequence information was available on the protein. The main objective of this thesis was to obtain the eDNA and the primary amino acid sequence for suGFI. Using this information, additional aims were to determine the developmental distribution of the protein and obtain insight into the molecular basis of the regulatory function of suGF 1 by analysis of the primary protein structure and expression of the eDNA.